Intellectual Capital, Corporate Social Responsibility, and Good Corporate Governance Effects on Stock Price Performance in the Indonesian Banking Sector - Abdul Salam; Tiara Dwi Aryanti (Politeknik Ganesha Medan, 2026)
This study investigates the effects of CSR and GCG on stock price performance, with Intellectual Capital (IC) serving as a mediating variable in Indonesian banking sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Grounded in Stakeholder and Signaling Theory, the Resource-Based and Knowledge-based view. The study argues that sustainability and governance practices enhance market value through the development of strategic knowledge-based resources. A quantitative explanatory research design was employed using panel data collected from 10 banking firms, selected through purposive sampling. The data were analyzed, used panel data regression and Sobel mediation tests implemented in STATA version 17. The findings indicate that CSR and GCG don’t exert a significant direct impact on stock price performance, suggesting that investors do not immediately translate sustainability and governance initiatives into market valuation. In contrast, IC demonstrates a positive and significant impact on stock price performance, highlighting its role as a critical intangible asset and a source of sustainable competitive advantage. Furthermore, both CSR and GCG significantly contribute and the enhancement of IC through the strengthening of human, structural, and relational capital. Mediation analysis affirm that IC fully mediates the relationships between CSR and stock price performance as well as between GCG and stock price performance. These findings underscore the strategic importance of IC as the primary mechanism through which sustainability and governance practices create market value and improve stock market performance in the banking sector.